A new heat flux model for the Antarctic Peninsula incorporating spatially variable upper crustal radiogenic heat production. Issue 11 (12th June 2017) - Burton‐Johnson, A.; Halpin, J. A.; Whittaker, J. M.; Graham, F. S.; Watson, S. J.
Abstract: A new method for modeling heat flux shows that the upper crust contributes up to 70% of the Antarctic Peninsula's subglacial heat flux and that heat flux values are more variable at smaller spatial resolutions than geophysical methods can resolve. Results indicate a higher heat flux on the east and south of the Peninsula (mean 81 mW m −2 ) where silicic rocks predominate, than on the west and north (mean 67 mW m −2 ) where volcanic arc and quartzose sediments are dominant. While the data supports the contribution of heat‐producing element‐enriched granitic rocks to high heat flux values, sedimentary rocks can be of comparative importance dependent on their provenance and petrography. Models of subglacial heat flux must utilize a heterogeneous upper crust with variable radioactive heat production if they are to accurately predict basal conditions of the ice sheet. Our new methodology and data set facilitate improved numerical model simulations of ice sheet dynamics. Plain Language Summary: As the climate changes, the Antarctic ice sheet represents the single largest potential source of sea level rise. However, one key parameter controlling how the ice sheet flows remains poorly constrained: the effect of heat derived from the Earth's geology on the base of the ice sheet (known as subglacial heat flux). Although this may not seem like a lot of heat, under slow‐flowing ice, this "heat flux" can control how well the ice sheet can flow over the rocks and even lead to melting of the ice at its base. Current models for Antarctica's heat flux use geophysics to determine how thin the crust is and consequently how easily heat from the Earth's mantle can warm the surface. We show here that heat produced by radioactive decay within the Earth's crust can have an even greater and much more variable contribution to the subglacial heat flux than estimated by these previous models. We present a new methodology allowing this crustal heat production to be calculated and combined with the geophysical models, producing a new map of heat flux on the Antarctic Peninsula highlighting the variations in heat flux caused by different rock types. Key Points: As a direct result of lithological heterogeneities in the upper crust, subglacial heat flux is much more variable than can be resolved by geophysical methods Upper crustal heat production on the Antarctic Peninsula contributes 6–70% of the total subglacial heat flux Sedimentary basins can produce comparably high heat fluxes to granitic intrusions; coupled with their erodible nature, these basins may impart a greater control on ice sheet dynamics than previously recognized